2008
DOI: 10.1063/1.2981209
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon enhanced Förster resonance energy transfer between the CdTe quantum dots

Abstract: Förster resonance energy transfer ͑FRET͒ between CdTe quantum dots ͑QDs͒ at nanoscale proximity to gold nanoparticle ͑Au NP͒ layers is investigated experimentally. We have observed the enhancement in the acceptor QDs' photoluminescence lifetime intensities. The decrease in donor QDs' exciton lifetime from 5.74 to 2.06 ns, accompanied by an increase in acceptor QDs' exciton lifetime from 3.38 to 7.52 ns, provided evidence for enhanced FRET between the QDs near Au NPs. The Au NPs' surface plasmon dipole fields a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
86
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 26 publications
(25 reference statements)
4
86
0
Order By: Relevance
“…6,[19][20][21][22][23][24][25][26][27][28][29] LSP coupled FRET has been observed using single metallic nanoparticles coupled to a single donor-acceptor pair 6 , core-shell structures [23][24][25] and planar structures. [26][27][28] Studying FRET from a conjugated polymer to fluorescent multilayer core-shell NP, Lessard-Viger et al observed a 70% increase in the Förster radius and an increase in the FRET-rate by two orders of magnitude. 24 Also using a core-shell geometry, composed of donor and acceptor fluorophore molecules embedded in a shell coating a Au-Ag core-shell nanocrystal, Wang et al demonstrated that FRET could be switched on and off by varying the spectral position of the LSP resonance relative to the donor emission and acceptor absorption.…”
Section: Introductionmentioning
confidence: 99%
“…6,[19][20][21][22][23][24][25][26][27][28][29] LSP coupled FRET has been observed using single metallic nanoparticles coupled to a single donor-acceptor pair 6 , core-shell structures [23][24][25] and planar structures. [26][27][28] Studying FRET from a conjugated polymer to fluorescent multilayer core-shell NP, Lessard-Viger et al observed a 70% increase in the Förster radius and an increase in the FRET-rate by two orders of magnitude. 24 Also using a core-shell geometry, composed of donor and acceptor fluorophore molecules embedded in a shell coating a Au-Ag core-shell nanocrystal, Wang et al demonstrated that FRET could be switched on and off by varying the spectral position of the LSP resonance relative to the donor emission and acceptor absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced local field generated by the plasmonic structures has also been shown to facilitate plasmon-enhanced nonradiative energy transfer. This has been demonstrated in a variety of material systems and geometries, with reported enhancements of the nonradiative energy transfer distance, rate and efficiency [26][27][28][29][30][31][32][33]. The possibility to achieve higher energy transfer efficiencies over larger distances allows for nonradiative pumping of a larger volume of QDs, and can potentially be exploited to improve the efficiency of nonradiatively pumped down-conversion for white LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Förster resonance energy transfer (FRET) [1,2] between spacially separated donor and acceptor fluorophores, e.g., dye molecules or semiconductor quantum dots (QD), underpins diverse phenomena in biology, chemistry and physics such as photosynthesis, exciton transfer in molecular aggregates, interaction between proteins [3, 4] or, more recently, energy transfer between QDs and in QD-protein assemblies [5][6][7]. FRET spectroscopy is widely used, e.g., in studies of protein folding [8,9], live cell protein localization [10,11], biosensing [12,13], and light harvesting [14].During past decade, significant advances were made in ET enhancement and control by placing molecules or QDs in microcavities [15][16][17] or near plasmonic materials such as metal films and nanoparticles (NPs) [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. While Förster transfer is efficient only for relatively short donor-acceptor separations ∼10 nm [3], a plasmonmediated transfer channel supported by metal NPs [32][33][34][35][36][37], films and waveguides [35,38] or doped monolayer graphene [39], can significant increase the transition rate at larger distances between donor and acceptor.…”
mentioning
confidence: 99%
“…During past decade, significant advances were made in ET enhancement and control by placing molecules or QDs in microcavities [15][16][17] or near plasmonic materials such as metal films and nanoparticles (NPs) [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. While Förster transfer is efficient only for relatively short donor-acceptor separations ∼10 nm [3], a plasmonmediated transfer channel supported by metal NPs [32][33][34][35][36][37], films and waveguides [35,38] or doped monolayer graphene [39], can significant increase the transition rate at larger distances between donor and acceptor.…”
mentioning
confidence: 99%